Moral saints and moral exemplars - Schwartz, Michael; Harris, Howard (Emerald, 2013)
The purpose of the series is to explore the central and unique role of organizational ethics in creating and sustaining a pluralistic, free enterprise economy. The primary goal of the research studies published here is to examine how profit seeking and not for profit organizations can be conceived and designed to satisfy legitimate human needs in an ethical and meaningful way.
Keywords: Business ethics.; Business & Economics -- Business Ethics.; Business studies: general.; elektronické knihy; electronic books